A fuzzy-based leanness evaluation model for manufacturing organisations. Issue 11 (18th August 2021) - Amin, M. A.; Alam, M. R.; Alidrisi, H.; Karim, M. A.
Abstract: In order to evaluate and monitor the impacts of improvement initiatives in terms of the overall leanness level, it is important to identify right performance metrics to measure the current and desired leanness level. Currently, there is a lack of proper methodology to accurately measure the impact of implementation of lean strategies on overall leanness of an organisation. This paper proposes an effective leanness measurement model using the triangular linguistic fuzzy membership function. The effectiveness of the model was demonstrated by a case study. The leanness value of the organisation before implementing lean was 0.12, which was improved to 0.19 after implementing a lean tool. The optimum leanness value of that organisation was calculated to be 0.64. These leanness values provided a quantitative indication of the impacts of improvement initiatives in terms of the overall leanness level, which was found to be highly beneficial as recognised by the case organisation.